Amylose-Free ("waxy") Wheat Colonization by Fusarium spp. and Response to Fusarium Head Blight - Funnell-Harris, Deanna L (Plant disease, 2019)
Hexaploid waxy wheat (Triticum aestivum L.) has null mutations in Wx genes and grain lacking amylose with increased digestibility and usability for specialty foods. The waxy cultivar Mattern is susceptible to Fusarium head blight (FHB) caused by Fusarium graminearum species complex, which produces the mycotoxin deoxynivalenol (DON). In experiment 1, conducted during low natural FHB, grain from waxy breeding lines, Mattern, and wild-type breeding lines and cultivars were assessed for Fusarium infection and DON concentration. Nine Fusarium species and species complexes were detected from internally infected (disinfested) grain; F. graminearum infections were not different between waxy and wild-type. Surface- and internally infected grain (nondisinfested) had greater numbers of Fusarium isolates across waxy versus wild-type, but F. graminearum-like infections were similar; however, DON levels were higher in waxy. In experiment 2, conducted during a timely epidemic, disease severity, Fusarium-damaged kernels (FDK), and DON were assessed for waxy breeding lines, Mattern, and wild-type cultivars. Disease severity and FDK were not significantly different from wild-type, but DON was higher in waxy than wild-type lines. Across both experiments, waxy breeding lines, Plant Introductions 677876 and 677877, responded similarly to FHB as moderately resistant wild-type cultivar Overland, showing promise for breeding advanced waxy cultivars with reduced FHB susceptibility